2013
DOI: 10.1002/chem.201300282
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Photoresponsive Supramolecular Assemblies Based on Diarylethene

Abstract: Scheme 1. a) Molecular-modeled structures (view from the thiophene rings) of a diarylethene derivative in the open (left) and the closed form (right). Moieties of 1, ÀC 6 H 4 ÀCONHÀOPV, are replaced with phenyl groups for clarity. In the open form, round arrows indicate the rotation of thiophene rings and the accompanying motion of the methyl groups. In the closed form, arrows indicate the direction of the conformationally fixed methyl groups. b) Structures of OPV-equipped diarylethene 1 in the open (1 o) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 71 publications
(24 reference statements)
0
31
0
Order By: Relevance
“…Yagai and coworkers have demonstrated that compound 4 ( Fig. 3) in the flexible open form more inclines to aggregate compared to the rigid closed form [29]. This is mainly due to the aggregation of compound 4 is driven by strong π-π stacking interaction between the two π-conjugated wings, and the steric effect of the two methyl groups of the diarylethene core of the closed isomer prevents the aggregation.…”
Section: Diarylethenes As Photoresponsive Building Blocks In Supramolmentioning
confidence: 92%
“…Yagai and coworkers have demonstrated that compound 4 ( Fig. 3) in the flexible open form more inclines to aggregate compared to the rigid closed form [29]. This is mainly due to the aggregation of compound 4 is driven by strong π-π stacking interaction between the two π-conjugated wings, and the steric effect of the two methyl groups of the diarylethene core of the closed isomer prevents the aggregation.…”
Section: Diarylethenes As Photoresponsive Building Blocks In Supramolmentioning
confidence: 92%
“…The effects of such changes were demonstrated by Yagai et al in a study of the DTE gelator 32. 341 In its closed form, the compound gives rise to non-fluorescent solutions in methylcyclohexane, but ring opening under 600 nm light produces a highly fluorescent gel within one minute. Molecular modelling suggests that the photoproduct can selfassemble into ordered π-π stacked aggregates, with efficient migration of excitation energy leading to strong emissivity (Fig.…”
Section: Articlementioning
confidence: 99%
“…Therefore, the open-form of C 3 -BTE is favorable for the formation of ordered self-assemblies, while the central methyl groups in the closed-form hamper the stacking of molecules in one direction. [ 12 ] In summary, we synthesized a C 3 -symmetric diarylethenes modifi ed BTA molecule C 3 -BTE, which could have reversible photochromic isomerization resulting in tunable self-assembly morphology. It can self-assemble in toluene solvent into microrods via synergistic H-bonding and π-stacking interactions.…”
Section: Communicationmentioning
confidence: 99%
“…[ 11 ] Yagai et al reported OPV-equipped diarylethene, [ 12 ] whose aggregation was driven by π-π stacking interaction which required close contact of building blocks, showing the higher aggregation ability in the fl exible open form compared with the rigid closed one. This is presumably considered that the two methyl groups can work as regulators for aggregation, as they are mobile by the rotation of thiophene rings in the open form, whereas in the closed form they are fi xed toward stacking direction.…”
mentioning
confidence: 99%